Delivery Route Estimation on a Web-Based Restaurant Delivery System Using Greedy Algorithm - Wando, Carmelita Margaretha Jawa; Dzikria, Intan (Journal of Information Technology and Cyber Security, 2023)
Food delivery application services have been significantly developed in Indonesia. However, several areas have not received application services like this. Orders made by several restaurants still use social media such as Whatsapp, Facebook, and cell phones. Traditional ordering does not have sufficient means to calculate the cost of delivery of orders resulting in cost-efficiency problems. In addition, order delivery routes are a problem for couriers who have to deliver several orders at once. This research builds a web-based restaurant delivery system by applying a greedy algorithm to optimize routes and shipping costs. The results of this study indicate that the greedy algorithm can determine the best route for couriers to make deliveries so that shipping costs become lower. This research contributes as one proof of the application of the greedy algorithm to business problems and restaurants may use the resulting system to increase the effectiveness of order delivery.